2021
DOI: 10.1016/j.heliyon.2021.e06547
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with age of mother at first birth in Albania: application of quantile regression model

Abstract: The objective of this study was to explore the risk factors that can determine the age of mother at first birth in Albania. The necessary information was extracted from a nationally representative sample survey, Albania Demographic and Health Survey, 2017-18 dataset. To identify the possible risk factors of the age of mother at first birth, we applied quantile regression model. The mean age of mother at first birth was found to be 22.38 years with standard deviation of 3.56 years. The minimum and maximum age w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Participants' age at menarche was found to be 12-13 years old in about less than half (43.9%) of the participants and more than 14 years old in (28.9%) of the participants, similar findings were reported in the parallel study which found that the mean age at menarche was found to be 12.4 years old [23]. Age at first live birth was found to be 20-24 in about half (50.5%) of the participants analogous findings were reported in a congruent study carried out by Talukder et al in which the mean maternal age at first life birth was found to be 22.38 years old [24]. Only 5% of the participants had a breast biopsy.…”
Section: Figure 2: Participants' Perception Of the Suitable Age For B...supporting
confidence: 86%
“…Participants' age at menarche was found to be 12-13 years old in about less than half (43.9%) of the participants and more than 14 years old in (28.9%) of the participants, similar findings were reported in the parallel study which found that the mean age at menarche was found to be 12.4 years old [23]. Age at first live birth was found to be 20-24 in about half (50.5%) of the participants analogous findings were reported in a congruent study carried out by Talukder et al in which the mean maternal age at first life birth was found to be 22.38 years old [24]. Only 5% of the participants had a breast biopsy.…”
Section: Figure 2: Participants' Perception Of the Suitable Age For B...supporting
confidence: 86%
“…In addition, the QR model yielded more unbiased estimates for skewed data than the linear regression model [33]. Previous studies applied the QR model for exploring the contributing factor of the age of the mother at first birth and age at first marriage because of its non-normality nature [34][35][36]. Moreover, several researchers applied the QR model to examine the core socio-demographic factors of child nutritional status [37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…This might have a connection with maternal age at first birth, which is below 20 years in the Ethiopian context [ 64 ]. Thus, as maternal age at first birth increases the chance of school dropout is reduced and this paves the way to obtain vocational skills that improve the economic status of the mother, her child, and the family as well [ 65 ]. Nevertheless, there is ample evidence suggesting that women who are 35 years and above will have adverse maternal and fetal outcomes [ 41 , 66 ].…”
Section: Discussionmentioning
confidence: 99%